Adalimumab induced psoriasis in Crohn’s disease and treatment with ustekinumab: case report and special histopathological findings - Qiu, Fang; Chen, Weiquan; Zhou, Ying (Frontiers in Medicine, 2025)
This case report presents an instance of Tumor Necrosis Factor-α Inhibitor-induced psoriasis (TNFiIP), also known as paradoxical psoriasis, in a 30-year-old male with fistulizing Crohn’s disease. The patient developed extensive erythematous and scaly lesions on the palms, lower limbs, ankles, and soles after 4 months of adalimumab monotherapy. Histopathological analysis revealed a pattern of psoriasiform dermatitis with notable dermal neutrophil and eosinophil infiltration, distinguishing TNFiIP from idiopathic psoriasis. The patient’s condition significantly improved following the transition from adalimumab to ustekinumab, which highlights the importance of alternative therapeutic strategies for patients who exhibit paradoxical reactions to TNF-α inhibitors.